Design, Manufacture, and Performance Testing of a Water Hammer Pump with Five Different Air Chambers - Marco Fidel Romero Zárate; Héctor Flores-Breceda; Juan Arredondo-Valdez; Urbano Luna-Maldonado; Wilgince Apollon; Alejandro Isabel Luna-Maldonado (Turkish Journal of Agriculture: Food Science and Technology)
The water hammer pump presents a promising solution for water supply in water-scarce regions. In Mexico, despite abundant overall water resources, many arid areas still lack access to reliable water. This study focused on optimizing the design and performance of low-cost water hammer pumps, which are powered by river currents and require minimal maintenance. While these pumps offer a sustainable solution, they face challenges such as water wastage, noise, and potential for low efficiency. Specifically, this research aimed to evaluate the impact of air chamber design on pump performance. The materials used in the prototype included steel pipes, steel plates, connectors, and lift valves for the air chambers. The pump itself utilized steel reducers, elbows, bronze waste valves, and a steel frame. Testing materials comprised plastic hoses, a digital stopwatch, an overhead tank, graduated cylinders, and plastic buckets. During the design phase, water flow rate, head height, and pipe diameters were taken into account. The Michaud-Venso formula and Allievi's equation were used to calculate pressure and wave velocity. A prototype featuring welded air chambers and waste valves was fabricated for functional testing. Laboratory performance tests were conducted using a 0.15 m³ tank at 1.0 m and 1.2 m heights, with 52 mm and 76 mm inlet pipe diameters. The pump's power output was not measured. Specifically, air chamber sizes of approximately 2690 cm³ resulted in a 15% increase in performance. The lowest efficiency, 5%, for a 76 mm waste valve, occurred with an 880 cm³ air chamber, while the highest efficiency (17.0%) was achieved with a 6108 cm³ air chamber. The volume of water collected at the outlet was dependent on the air chamber size. As the air chamber volume increased, the flow rate at the inlet valve also increased. Therefore, optimally sizing both air chambers and waste valves is significant to maximizing pump efficiency.